From exhaustion to insight: Uncovering the antecedents of work stress among healthcare professionals. - Yiğit, Ayşenur Baysal; Toker, Kerem (Work, 2025)
Background: In the post-COVID period, the work stress experienced by healthcare professionals has become a more questionable problem. Existing studies generally examine factors caused by work stress. Few studies and discussions are identifying the antecedents of work stress. Objective: This study aims to uncover the underlying factors contributing to work stress among healthcare professionals. Among these antecedents, we examined the effect of innovative work behavior, contextual business performance and discussed the moderating role of ergonomics. Methods: The study sample consisted of 177 health professionals over 18 working in hospitals operating in Istanbul. We collected data from healthcare professionals through sociodemographic information form, work stress scale, innovative work behavior scale, and contextual business performance scale. We analyzed the data by partial least squares structural equation modeling (PLS-SEM) using the Smart PLS 4.0 software package. Results: As a result, the research findings suggest contextual business performance, potentially affected by innovative work behaviour and moderated by ergonomics, can be a critical antecedent of work stress. Conclusion: Health administrators who desire to reduce employees' work stress need to develop a theoretical and practical understanding of innovative work behaviour, contextual business performance, and ergonomics. Hence, discovering the causal mechanism behind work stress fills an essential gap in the literature.